Teachers' perspectives on implementing microlearning in numeracy literacy in elementary schools - Haliem, Theresa Dwita; Murti, Rahayu Condro; Wibowo, Setiawan Edi; Suryani, Lilis (Jurnal Prima Edukasia, 2026)
This study aims to describe the current conditions of numeracy literacy learning in elementary schools and analyze the needs for developing microlearning-based e-modules as an innovative solution to support the implementation of the Merdeka Curriculum. The study was motivated by the fact that numeracy instruction in schools remains dominated by traditional approaches, with limited integration of contextual digital media and minimal innovation in teaching practices. A descriptive qualitative approach was applied, involving five elementary schools in the Moyudan District, Sleman Regency, Yogyakarta Special Region. Participants consisted of five fifth-grade teachers and 83 students selected through purposive sampling. Data were collected through classroom observations, semi-structured interviews, and documentation, and analyzed using the Miles and Huberman interactive model. The findings revealed that while teachers recognize the importance of strengthening numeracy literacy as a 21st-century competence, they face various challenges, including limited time, insufficient digital pedagogical training, and the unavailability of relevant learning materials. The results highlight that the microlearning approach is pedagogically relevant because it provides concise, contextual, and interactive learning experiences that enhance students’ conceptual understanding and engagement. The study concludes that developing microlearning-based e-modules has significant potential to improve the quality of numeracy literacy learning in elementary schools, supporting a more adaptive, participatory, and technology-integrated learning environment.